Pengembangan Prototipe Sistem Korespondensi Digital Universitas Atma Jaya Makassar - Sjarif, Adi Chandra (TEMATIKA, Journal of Informatics and Information Systems, 2013)
Internal communication has been the corner stone of any organization operations. Traditionally, paper based communication is the fundamental ways of doing things for many organizations and this is also true for University of Atma Jaya Makassar. With the increasingly competitive business environment, digital communication system proofs its importance to tackle ineffective and various problems arise from the traditionally paper based communication system. Employing prototype software development method, the prototype of digital communication system for University of Atma jaya Makassar is designed to handle internal communication, standardize communication method and reduce cost of communication. The resulting system is structured based on the ongoing paper based communication structure and integrated through the existing local area network as well as application platform